A hybrid MCDM approach to assess the sustainability of students’ preferences for university selection - Kabak, Mehmet; Dağdeviren, Metin (Technological and Economic Development of Economy, 2014)
Selection of the most suitable university among many alternatives is a multi-criteria decision making (MCDM) problem. In this paper, an integrated approach which employs analytic network process (ANP) and preference ranking organization method for enrichment evaluations (PROMETHEE) together, is proposed for this problem. By the way, the paper is concerned with criteria influencing student choice in Turkey to establish if there is any need in developing a multi-criteria model for predicting students’ preference for universities. The ANP is used to analyse the structure of the university selection problem and to determine weights of the criteria, and the PROMETHEE method is used to obtain final ranking, and to make a sensitivity analysis by changing the weights for criteria. The results indicate that three factors, future career prospects and opportunities, scholarship and university’s social life at the top in the university selection. First published online: 11 Aug 2014